Determinants of the lost to follow-up status among patients with tuberculosis who emigrated to the Republic of Korea: a mixed-method study - Jeon, Sumin; Lee, Ji Yeon; Jeong, Ina; Sin, Sooim; Lee, Inhan; Kim, Younghyun; Han, Ah Yeon; Lee, Seung-Eun; Seo, Soonryu; Kim, Hyungjun; Kwon, Yunhyung; Song, Chieeun; et al. (Frontiers in Public Health, 2025)
IntroductionTuberculosis (TB) remains a significant global health concern, with foreign migrants in the Republic of Korea (ROK) representing a particularly vulnerable group; despite comprising only 3.5% of the population, they account for over 5% of annual TB cases and exhibit disproportionately high rates of lost to follow up (LTFU) from treatment compared to native Koreans. This mixed-methods study aimed to identify key factors influencing non-adherence to treatment and LTFU among migrants.MethodsUtilizing national TB surveillance data from 2016 to 2018 for 4,011 migrant and 64,620 native patients, quantitative analysis were employed to identify factors associated with LTFU for migrants. Complementary in-depth qualitative interviews with Public-Private Mix (PPM) nurses provided deeper insights into barriers to adherence.ResultsThe study revealed a significantly higher LTFU rate (21.5%) among migrant patients compared to domestic patients (2.3%). Key contributing factors included nationality (highest crude odds for migrants from Thailand, Central, and North Asia), living arrangements (increased risk for those not with family or living alone), and male gender. Drug-resistant TB made patients over four times more likely to discontinue treatment and systemic issues such as frequent care transfers and the presence of comorbidities. Qualitative findings highlighted inadequate patient education and misconceptions about TB severity (often seen as a “mild cold”), leading to premature discontinuation. Poor medical interpretation services and low awareness among migrants of free TB treatment under the PPM program were also critical barriers.DiscussionThese findings imply that high LTFU among migrant patients is multifactorial, stemming from personal, clinical, and systemic issues. Addressing this disparity requires targeted interventions, including culturally tailored multilingual educational campaigns, improved medical interpretation, and increased awareness of PPM program eligibility and free treatment. Streamlining interfacility care transfer processes (such as the “Tuberculosis Relief Belt” initiative), expanding PPM coverage, and ensuring access to specialized care for comorbid conditions are also essential. Addressing these multifaceted challenges is critical to reducing LTFU rates and enhancing treatment continuity and outcomes, thereby advancing TB control efforts in ROK’s shifting migration context.